The importance of modern digital technologies in the Jordanian film industry The movie "Captain Abu Raed" as a model - Alfaleh, Ahmad; fayad, Ali (Dirasat: Human and Social Sciences, 2022)
Modern digital technologies in cinema have added a great development in many fields; the most important of which is the field of cinematography, lighting, and the field of film editing. This research highlights the important role of these technologies in the development of the Jordanian digital cinematic film industry by analyzing one film as a sample, the Jordanian digital film "Captain Abu Raed", which used modern digital technologies in its production in cinema in 2008. The film is analyzed qualitatively and the role of modern digital technologies in making is examined. The research consists of four sections, where the first section includes the definition of the research problem, objectives, significane, the procedural definitions, and the research sample. The second section includes the theoretical framework for the research, where the research discusses the importance of modern digital technologies in Jordanian cinema and their development, and presents a theoretical framework regarding the basic elements in digital cinematography as follows: cinematography, lighting, and film editing. The third section also analyzes the research sample, which is a Jordanian digital cinematic film "Captain Abu Raed", and it highlights the digital technical aspects in its production. The fourth section includes the research results related to the research.